2021
DOI: 10.1038/s41467-021-26058-5
|View full text |Cite
|
Sign up to set email alerts
|

Wdr47, Camsaps, and Katanin cooperate to generate ciliary central microtubules

Abstract: The axonemal central pair (CP) are non-centrosomal microtubules critical for planar ciliary beat. How they form, however, is poorly understood. Here, we show that mammalian CP formation requires Wdr47, Camsaps, and microtubule-severing activity of Katanin. Katanin severs peripheral microtubules to produce central microtubule seeds in nascent cilia. Camsaps stabilize minus ends of the seeds to facilitate microtubule outgrowth, whereas Wdr47 concentrates Camsaps into the axonemal central lumen to properly positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…To confirm that ribosomal proteins can be readily identified from motile cilia, we purified multicilia from cultured mEPCs (Fig. 1a ) 23 , performed shotgun mass spectrometry 24 , and hit 95% of known ribosomal components (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm that ribosomal proteins can be readily identified from motile cilia, we purified multicilia from cultured mEPCs (Fig. 1a ) 23 , performed shotgun mass spectrometry 24 , and hit 95% of known ribosomal components (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…In non-centrosomal microtubules, WDR47/NMTN-1 protects CAMSAP2 against katanin-mediated severing and is required for axonal and dendritic development (Buijs, Hummel et al 2021). In mammalian multicilia, WDR47/NMTN-1 co-operates with CAMSAP family proteins and MT-severing enzyme katanin to generate ciliary central microtubules (Liu, Zheng et al 2021). WDR47/NMTN-1 also functions through CAMSAP3 to control neuronal migration and the early stages of neuronal polarization, which is important for neonatal mouse survival (Chen, Zheng et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We further demonstrated that WDR47/NMTN-1 ensures proper IFT particle movement and cargo delivery in the AWB neurons, promoting ciliogenesis. WDR47/NMTN-1 has been revealed as a microtubule-associated protein; it has been shown to interact with CAMSAP family proteins for microtubule-mediated processes (Chen, Zheng et al 2020, Buijs, Hummel et al 2021, Liu, Zheng et al 2021. In noncentrosomal microtubules, WDR47/NMTN-1 protects CAMSAP2 against kataninmediated severing and is required for axonal and dendritic development (Buijs, Hummel et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The architecture of polarized intestinal epithelial cells was only mildly affected, consistent with redundancy in apico-basal polarity organization ( Toya et al, 2016 ). Analysis of CAMSAP loss-of-function in invertebrate and vertebrate models has revealed a wide range of phenotypes such as axon and dendrite growth and branching defects, reduced cell survival and organ size, or loss of ciliary motility ( Chuang et al, 2014 ; Marcette et al, 2014 ; Richardson et al, 2014 ; Robinson et al, 2020 ; Liu et al, 2021 ; Yang and Choi, 2021 ). However, since CAMSAPs are likely general minus-end stabilizers rather than dedicated anchoring factors, some of these phenotypes may not necessarily result from anchoring defects, but, for example, from an overall reduction in microtubule density in CAMSAP-deficient cells ( Jiang et al, 2014 ).…”
Section: Consequences Of Microtubule Anchoring Defectsmentioning
confidence: 99%